The lost hero - Riordan, Rick (New York : Disney/Hyperion Books, 2010)
Jason, Piper, and Leo, three students from a school for "bad kids," find themselves at Camp Half-Blood, where they learn that they are demigods and begin a quest to free Hera, who has been imprisoned by Mother Earth herself
AR
Keywords: Hera -- (Greek deity) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Camps -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Monsters -- Juvenile fiction; Greek mythology -- Juvenile fiction; Monsters -- Juvenile fiction; Adventure stories, American; Occult fiction